1996
DOI: 10.1016/s0006-8993(96)00848-7
|View full text |Cite
|
Sign up to set email alerts
|

Nerve regeneration across a 25-mm gap bridged by a polyglycolic acid-collagen tube: a histological and electrophysiological evaluation of regenerated nerves

Abstract: In the study reported here we have examined the nerve regeneration that occurs over a 25-mm gap using a novel biodegradable nerve guide tube. The tube was a composite of polyglycolic acid (PGA) mesh coated with collagen which was filled with neurotrophic factors. The left sciatic nerve of ten adult cats was dissected. The stumps were connected by the tube, and fixed gap. Histological examinations carried out 4-16 months after implantation of the tube revealed regeneration of well vascularized nerve tissue. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 22 publications
2
84
0
5
Order By: Relevance
“…Japanese researchers using polymeric PGA mesh and collagen sponge inside the tube could reconstruct a peripheral nerve gap of about 3 cm. 32,33 This structure is shown in Figure 6.…”
Section: Composite Nerve Guidesmentioning
confidence: 99%
“…Japanese researchers using polymeric PGA mesh and collagen sponge inside the tube could reconstruct a peripheral nerve gap of about 3 cm. 32,33 This structure is shown in Figure 6.…”
Section: Composite Nerve Guidesmentioning
confidence: 99%
“…29,30 Some of these have proved to be more potent in promoting peripheral nerve regeneration if Schwann cells were introduced. 30,31 Schwann cells play an indispensable role in promoting regeneration in three ways: first, by increasing their synthesis of surface cell adhesion molecules (CAMs), such as N-CAM, Ng-CAM/L1, N-cadherin, and L2/HNK-1; second, by elaborating basement membrane that contains many extracellular matrix proteins, such as laminin (LN), fibronectin (FN), heparan sulphate proteoglycans (HSP), and tenascin; and third, by producing many neurotrophic factors and their receptors.…”
Section: Schwann Cell and Peripheral Nerve Regenerationmentioning
confidence: 99%
“…Apesar In spite of discordance (KIYOTANI et al, 1996;SUZUKI et al, 1999), several trials studied the axonal growth through empty tubes and concluded that 10 mm was the maximum distance to achieve an appropriate regeneration (BRUNELLI et al, 1994;DEN DUNNEN et al 1996;FRANCEL et al, 1997 (LUNDBORG et al 1982;WILLIAMS et al 1983;DA SILVA, 1987;LANGONE, 1991).…”
Section: ) We Chose Polyethylene Tubes Due To Their Availabilitymentioning
confidence: 99%